Risk assessment and RCM as a tool for technical regulation in Bolivian railways - Guzmán Ballivián, Javier (Univerzita Pardubice, 2007)
The aim of the thesis is to describe a methodological approach for evaluating railway safety in Bolivian rolling stocks.
Hodnocení rizik a RCM jako nástroj technického řízení železnic v Bolívii
Keywords: risk assessment; technical regulation; railways; Bolivia; Železnice; Bolívie; technické řízení; hodnocení rizik